Case report: Fatal Borna virus encephalitis manifesting with basal brain and brainstem symptoms - Lourbopoulos, Athanasios; Schnurbus, Lea; Guenther, Ricarda; Steinlein, Susanne; Ruf, Viktoria; Herms, Jochen; Jahn, Klaus; Huge, Volker (Frontiers in Neurology, 2024)
Background Since the first report of fatal Borna virus-1 (BoDV-1) encephalitis in 2018, cases gradually increased. There is a lack of diagnostic algorithm, and there is no effective treatment so far. Case presentation We report an acute BoDV-1 encephalitis in a 77-year-old female with flu-like onset, rapid progression to word-finding difficulties, personality changes, global disorientation, diffuse cognitive slowness, and gait ataxia and further deterioration with fever, meningism, severe hyponatremia, epileptic seizures, cognitive decline, and focal cortical and cerebellar symptoms/signs. The extensive diagnostic workup (cerebrovascular fluid, serum, and MRI) for (meningo-)encephalitis was negative for known causes. Our empirical common antiviral, antimicrobial, and immunosuppressive treatment efforts failed. The patient fell into coma 5 days after admission, lost all brainstem reflexes on day 18, remained fully dependent on invasive mechanical ventilation thereafter and died on day 42. Brain and spinal cord autopsy confirmed an extensive, diffuse, and severe non-purulent, lymphocytic sclerosing panencephalomyelitis due to BoDV-1, affecting neocortical, subcortical, cerebellar, neurohypophysis, and spinal cord areas. Along with our case, we critically reviewed all reported BoDV-1 encephalitis cases. Conclusion The diagnosis of acute BoDV-1 encephalitis is challenging and delayed, while it progresses to fatal. In this study, we list all tried and failed treatments so far for future reference and propose a diagnostic algorithm for prompt suspicion and diagnosis.